The composition of lower genital tract microbiota correlates with in vitro fertilization and frozen embryo transfer outcomes in women with polycystic ovarian syndrome - Tu, Yaoyao; Zhou, Zhiyang; Lu, Ye; Wei, Bin; Ge, Yingzhou; Ding, Guolian; Dong, Xi; Sheng, Jianzhong; Zhang, Yixiang; Jin, Li; Huang, Hefeng (Frontiers in Cellular and Infection Microbiology, 2025)
Adverse reproductive outcomes remain a significant concern for women of reproductive age with polycystic ovary syndrome (PCOS), yet the role of the lower genital tract (LGT) microenvironment has been largely overlooked. This study aimed to investigate the association between the LGT microbiome and the outcomes of in vitro fertilization and frozen embryo transfer (IVF-FET) in women with PCOS. A total of 191 reproductive-aged women undergoing assisted reproductive technology (ART) treatment between December 2018 and October 2021 were recruited. The LGT microbiota was profiled using 16S rRNA sequencing and analyzed in relation to ART outcomes and clinical parameters. Furthermore, cervical transcriptome sequencing was performed in a subset of PCOS patients to investigate whether LGT microbiota alterations were associated with functional changes in mucosal epithelial cells. The results demonstrate significant dysbiosis of the LGT microbiome in patients with PCOS, characterized by a reduction in Lactobacillus abundance. Among 72 PCOS patients undergoing IVF-FET, those with a relative Lactobacillus abundance of ≥50% (n = 57) exhibited significantly improved reproductive outcomes compared to those with Lactobacillus abundance <50% (n = 15). Elevated testosterone levels were identified as the most significant factor associated with a reduced abundance of Lactobacillus in PCOS patients. Transcriptomic analysis further revealed that the LGT microbiota was associated with maintaining mucosal epithelial barrier integrity and immune homeostasis in PCOS. In conclusion, the findings highlight that dysbiosis of the LGT microbiota may significantly influence reproductive outcomes in PCOS patients, emphasizing the importance of targeting the LGT microenvironment to improve ART success rates.